Natural history of amblyopia untreated owing to lack of compliance. Issue 5 (1st May 1999) - Simons, Kurt; Preslan, Mark
Abstract : AIMS: A prospective study of the efficacy of amblyopia treatment in preschool children has recently been called for, requiring an untreated control group. The present study assessed data from patients with amblyopia untreated owing to lack of compliance, or with amblyopia risk factors, to determine outcome. METHODS: Longitudinal data were obtained from 18 4–6 year old patients who had initially been screened for amblyopia, strabismus, and/or bilateral refractive error, failed to comply with prescribed treatment, and in whom amblyopia was detected at a rescreening approximately a year later. The data from three previous studies comparing outcome of patients compliant and non-compliant with amblyopia treatment were also reanalysed. RESULTS: One child of the 18, who wore glasses sporadically, showed some improvement in visual acuity in the amblyopic eye. Otherwise, no child showed an improvement, and seven of the 17 (41%) for whom visual acuities were available at both screenings showed a deterioration of visual acuity in the amblyopic eye, including three who apparently developed amblyopia for the first time. A child with an ametropic risk factor for amblyopia whose visual acuity was not obtained at the first screening and who was largely non-compliant presented with amblyopia at the second screening. The reanalysed data from the three previous studies demonstrated a significantly poorer visual acuity outcome in the amblyopic eye in the non-compliant patient groups than in the compliant groups in each study. CONCLUSION: Preschool children with amblyopia or its risk factors are at risk of having the current amblyopia deteriorate, or of developing amblyopia, if not treated. These results raise questions about the ethical acceptability of a prospective study of amblyopia treatment at these ages.